Data, Predictions, and Decisions in Support of People and Society - Horvitz, Eric (20th ACM SIGKDD Conference on Knowledge Discovery and Data Mining, 2014)
I will share directions and results enabled by the confluence of large-scale data resources, jumps in computational power, and advances in machine intelligence. I will focus on efforts that leverage learning and inference to help people with decisions, touching on work in transportation, medicine, public health, and interactive systems. I will present projects that center on using traditional sources of data, such as GPS data and electronic health records, as well as efforts that harness more exotic streams of information, including the use of planes in flight and anonymized behavioral data drawn from web services as large-scale sensor networks. I will conclude by discussing the promise of leveraging data, learning, and reasoning to enable new kinds of collaboration between people and machines to address challenges in science, society, and daily life.